REVOLUSI PEMBELAJARAN PPKn LEBIH SERU DAN EFEKTIF DENGAN TEKNOLOGI DIGITAL DI SD 2 JEPANG: Revolution of Learning PPKn More Fun and Efective with Digital Technology at SD 2 Jepang - Supriyantini, Supriyantini; Okta Afiana, Devi; Nasir, Muhammad Fikri Abdun (Al-Qalbu: Jurnal Pendidikan, Sosial dan Sains, 2025)
This study aims to examine the effectiveness of integrating digital technology in the teaching of Civic Education (PPKn) at SD 2 Jepang. Using a qualitative literature review method, the research analyzes the application of digital tools such as interactive apps, animated videos, and online quizzes in the learning process. The findings indicate that digital technology enhances student engagement, understanding of Pancasila values, and fosters a dynamic learning environment. However, challenges such as limited teacher digital literacy and the need for more integrated learning content were also identified. The study concludes that digital technology offers significant benefits for PPKn instruction, yet continuous efforts are required to ensure its effective and equitable implementation